Density Functional Theory Investigation on The Electronic Structure, Properties and IR Spectra of 9,10-Iphenylanthracene - Adeyemi, Owolabi J; Gambo, Hassan; Yusuf, Onimisi M; Abdulkadir, Gidado S; Haruna, Ali; Akinade, Bankole J; Onma, Akusu C; Madugu, Muhammed L; Usman, Sakinat L (Universitas Sanata Dharma, 2024)
9,10-Diphenylanthracene belong to a class of polymer-based materials featuring a π-bonded molecules (organic semiconductors). We conducted a theoretical investigation into 9,10-DPA in both neutral and ionic states using Density Functional Theory (DFT) implemented in the Gaussian 09 package. The calculations employed B3LYP/6-31+G(d) and B3LYP/6-311++G(d,p) basis sets. The study focused on evaluating structural properties, electronic properties, global chemical reactivity descriptors and IR spectra of 9,10-DPA. These assessments aimed to elucidate the reactivity, stability, and conductivity of this molecule. The results reveal that charging influences the structural, electronic, and global index of the molecule. The analysis of bond lengths and angles emphasized that the following bond length R(C7-H18), R(C8-H19), R(C12-H26) and R(C13-H27) exhibits greater bond energy and strength in both neutral and ionic stats because of having shorter bond length than the remaining regardless of the chosen basis set. In the case of energy gap, the anionic alpha molecular orbital exhibits lower stability of having the lowest energy gap of 1.3679eV, indicating higher reactivity and conductivity among the entire MO and is supported by a higher softness value (1.15eV) and higher chemical potential (1.39eV). The cationic beta molecule exhibited stronger electron-attracting power because of having higher electronegativity (9.00eV), lower chemical potential (-9.00eV) and higher electrophilicity index (36.81eV). The vibrational analysis shows that the anionic molecular state possessed the highest IR absorption which occurred at the frequency of 1346.96cm-1. Overall, the findings underscore the importance of charge state in enhancing the electronic properties and the reactivity of these molecules for various applications in the field of organic electronics.Keywords: 9,10-Diphenylanthracene, ionization potential, electron affinity, global chemical index, infrared spectra, density of state